1991
DOI: 10.1128/jvi.65.2.805-812.1991
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the very early transcribed baculovirus gene PE-38

Abstract: We have started to identify early viral RNAs that are transcribed at 1 h after inoculation to investigate the mechanism involved in the regulation of early gene expression of Autographa californica nuclear polyhedrosis virus (AcNPV). Cloned viral DNA fragments were hybridized to Northern (RNA) blots of polyadenylated RNA isolated from Spodoptera frugiperda cells at 1, 2, and 6 h postinfection to localize very early transcripts. Subsequently we prepared a cDNA library of polyadenylated RNA transcribed at 1 h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 53 publications
(47 reference statements)
3
68
0
2
Order By: Relevance
“…An upstream activating region. An examination of the AcMNPV genome demonstrated that the CNE constitutes the central part of a symmetrically arranged region located between the coding sequences of the divergently transcribed immediate early genes ie2 and pe38 [62] ( Figure 1B) ( Figure S4). Both ie2 and pe38 are transcriptional transactivators, participating in many processes, among which DNA replication (ie2 and pe38) and cell cycle arrest (ie2) [22].…”
Section: The Acmnpv Genome Is the Most Appropriate Model To Investigamentioning
confidence: 99%
“…An upstream activating region. An examination of the AcMNPV genome demonstrated that the CNE constitutes the central part of a symmetrically arranged region located between the coding sequences of the divergently transcribed immediate early genes ie2 and pe38 [62] ( Figure 1B) ( Figure S4). Both ie2 and pe38 are transcriptional transactivators, participating in many processes, among which DNA replication (ie2 and pe38) and cell cycle arrest (ie2) [22].…”
Section: The Acmnpv Genome Is the Most Appropriate Model To Investigamentioning
confidence: 99%
“…Furthermore, IE1 is able to inhibit expression of the ie2 and ie0 promoters (7,21). The putative regulatory functions of other early viral genes like pe38 (23), me53 (19), and cg30 (39) are based on sequence analysis. The amino acid sequence of the protein encoded by the pe38 gene contains putative DNA binding and dimerization domains (23).…”
mentioning
confidence: 99%
“…The cells were scanned under a confocal microscope. tion start site (Blissard & Rohrmann, 1989;Chisholm & Henner, 1988;Guarino & Summers, 1986;Guarino & Summers, 1987;Krappa & Kenbel, 1991). The promoters of most late and very late genes have typically TAAG motifs and their transcriptions are mediated by alphaamanitin-resistant RNA polymerase (Blissard & Rohrmann, 1990;Morris & Miller, 1994).…”
Section: Discussionmentioning
confidence: 99%